C-reactive protein is related to future cognitive impairment and decline in elderly individuals with cardiovascular disease. (March 2017) - Weinstein, Galit; Lutski, Miriam; Goldbourt, Uri; Tanne, David
Highlights: We explored the association between inflammation and future cognition in individuals with a history of cardiovascular disease. Increased plasma CRP levels were associated with poorer cognitive performance overall and in executive function and attention domains. A greater decline in cognition was observed in participants with high vs. low CRP. These associations were independent of vascular risk factors and markers of cerebrovascular disease. Abstract: Aims: To explore the association of C-reactive protein (CRP) plasma levels with subsequent cognitive performance and decline among elderly individuals with pre-existing cardiovascular disease (CVD), and to assess the role of cerebrovascular indices in this relationship. Methods: CRP levels were measured in a subgroup of individuals with chronic CVD, who previously participated in a secondary prevention trial. Cognitive performance was evaluated 14.7 ± 1.9 and 19.9 ± 1.0 years after entry to the trial. A validated set of computerized cognitive tests was used (Neurotrax Computerized Cognitive Battery) to assess performance globally and in memory, executive function, visuospatial and attention domains. Linear regression and mixed models were used to assess the relationship of CRP plasma levels with cognitive scores and decline, respectively. In addition, we tested whether cerebrovascular reactivity, carotid intima media thickness and presence of carotid plaques modify these associations. Results: Among 536 participants (mean age at the first cognitive evaluation 72.6 ± 6.4 years; 95% males), CRP at the top tertile vs. the rest was associated with subsequent poorer performance overall (ß = −2.2 ± 1.0; p = 0.031) and on tests of executive function and attention (ß = −2.3 ± 1.1; p = 0.043 and ß = −2.0 ± 1.4; p = 0.047, respectively). Moreover, CRP levels were positively related to a greater decline in executive functions (ß = −2.4 ± 1.1; p = 0.03). These associations were independent of potential confounders and were not modified by cerebrovascular indices. Conclusion: Our findings suggest that systemic chronic inflammation, potentially associated with underlying atherosclerosis, is related to cognitive impairment and decline two decades later, in elderly individuals with pre-existing CVD.